Stable closure of acute and chronic wounds and pressure ulcers and control of draining fistulas from osteomyelitis in persons with spinal cord injuries: non-interventional study of MPPT passive immunotherapy delivered via telemedicine in community care - Sams-Dodd, Jeanette; Belci, Maurizio; Bandi, Surendra; Smith, Damian; Sams-Dodd, Frank (Frontiers in Medicine, 2024)
Background MPPT (micropore particle technology) is a topical wound treatment. It is a passive immunotherapy, acting via the skin and wound microbiome without use of antimicrobial action. In a general patient population, it removed wound infections 60% and initiated tissue regeneration 50% quicker than antibiotics and antiseptics. As MPPT acts by supporting the immune system, the aim was to confirm that MPPT is also effective in immunocompromised individuals. Spinal cord injured (SCI) persons are immunodeficient due to their injury and not an underlying disease, and recruit 50% fewer immune cells to an injury. The study therefore determined efficacy, safety, health-economics, and sustainability of MPPT in acute and chronic wounds and pressure ulcers in this patient population. Methods Pressure ulcers in SCI-persons is an orphan indication, patient variability is high, and ICH E10 excludes comparators due to ethical concerns. Study design was therefore a single-arm non-interventional, observational, post-market surveillance study of MPPT for treating wounds and pressure ulcers and removing soft tissue infection in connection with draining fistulas in SCI-persons. The study was based on telemedicine in community care. Results The study included 44 wounds. All acute and chronic grade 1-4 wounds and pressure ulcers reached stable closure. In wounds acting as fistulas draining from an underlying, primary focus of infection, e.g. osteomyelitis, MPPT removed the soft tissue infection in approx. 2.5 months and supported regeneration, considerably reducing fistula sizes. Compared to standard care, per wound cost-savings were 51% to 94% depending on wound grade and age and substantial nursing resources were freed up. The telemedicine approach was well received by participants and supported independence and self-care. The use of antimicrobials, plastics and synthetic polymers was essentially eliminated. MPPT did not require bed rest. Conclusion The study confirmed that MPPT is safe and effective in treating acute and chronic wounds in immunocompetent and immunocompromised individuals, including wounds with antimicrobial resistant infections. MPPT also removes soft tissue infections caused by an underlying primary focus of infection such as osteomyelitis. Non-healing wounds currently represent an unmet clinical need. The findings suggest that a therapy acting via the microbiome without antimicrobial actions is effective.